Trodusquemine enhances Aβ42 aggregation but suppresses its toxicity by displacing oligomers from cell membranes - Ryan Limbocker (Nature Portfolio, 2019)
Transient oligomeric species of the amyloid-β peptide (Aβ42) have been identified as key pathogenic agents in Alzheimer’s disease. Here the authors find that the aminosterol trodusquemine enhances Aβ42 aggregation and suppresses Aβ42-induced toxicity by displacing oligomers from cell membranes.